Eksplorasi dan Inventarisasi Tumbuhan Obat Berbasis Kearifan Lokal Masyarakat Dompu - Muharyati, Yully; Khatimah, Ainul (Jurnal Biosilampari : Jurnal Biologi, 2025)
This study aims to document and record the diversity of medicinal plant species, the diseases they are used to treat, methods of preparation and administration, plant parts utilized, sources of plant materials, plant species use value Spesies (UVs). An exploratory survey was conducted using a qualitative research approach. The study identified 42 species belonging to 23 families, with Zingiberaceae being the most represented family (6 species). A total of eight types of traditional medicines were recorded, used to treat 26 categories of diseases. The most commonly utilized plant parts were fruits (32.22%), while stems and bark were the least used (2.22%). The most frequent method of preparation was pounding (33.33%), whereas frying and boiling were the least common (5.56%). The dominant route of administration was oral consumption (30%), while eating and hair washing were the least frequent (5%). In terms of acquisition, most medicinal plants were purchased (41.86%), while wild collection (18.60%) was the least practiced. Based on the calculation of species use value spesies (UVs), the highest values were recorded for black glutinous rice, coconut, and nutmeg (UVs = 0.33), whereas the lowest were observed for dill (Anethum graveolens L) and papaya (UVs = 0.02).